Ferreira, D. F. (2018). Rebelião e reforma prisional em São Paulo: uma história da fuga em massa na Ilha Anchieta em 1952. Editora Revan. 304 pp. - González Alvo, Luis (Letras Históricas E-ISSN: 2448-8372, 2023)
Reseña de libro.